Inga edulis fruits: a new source of bioactive anthocyanins. Issue 19 (1st October 2020) - Lima, N. M.; Falcoski, T. O. R.; Silveira, R. S.; Ramos, R. R.; Andrade, T. J. A. S. A.; Costa, P. I.; La Porta, F. A.; Almeida, M. V. A.
Abstract: The extraction conditions and chromatographic analysis from seeds of Inga edulis were optimized and provided one anthocyanin from aqueous fraction and a mixture of three anthocyanins from methanolic fraction. The pure anthocyanin obtained was subjected to structural modifications and the products obtained were subjected to chemical and pharmacological assays, as well as quantum chemical calculations based on DFT and TD-DFT methods. Hence, the anthocyanin fractions were evaluated for their chemical-pharmacological potential through chemical and biological assays: antioxidant activity by the DPPH, determination of the Solar Protection Factor (SPF) and cytotoxic activity (hepatocellular carcinoma infected with hepatitis C virus). The results indicated that even the anthocyanin and derivatized compounds having high antioxidant potential showed an SPF lower than six, which is lower than the minimum accepted by current Brazilian legislation. In addition, none of compounds presented significant cytotoxic activity against the tumour cell line studied. Graphical Abstract: